Cheater identification in threshold scheme - DUAN Xiao-yi1; QI Wen-hua1; ZHANG Qi-shan1; WANG Zhong-wen2 (Tongxin xuebao)
A scheme can detection cheater correctly is proposed.The quantity of the scheme is detection and cheater identification efficient and simple.The attack is as difficult as factoring the product of large numbers.